RECONSTRUCTION OF STRONG WOMEN IN RACHEL PLATTEN'S SONG ‘GIRLS’: A FEMINIST CRITICAL DISCOURSE ANALYSIS - Fatimah Al Azizah; Griselda Gian Heris Herdina; Irma Khoirot Daulay (Universitas Mahaputra Muhammad Yamin, 2026)
This study looks at how the representation of strong women in popular culture is reconstructed in Rachel Platten's song Girls (2023). Prior research on women's representation in pop music has mostly concentrated on linguistic characteristics, moral principles, or themes of general empowerment. Feminist Critical Discourse Analysis (FCDA) has been used to examine how feminist ideology and female agency are discursively constructed in song lyrics. In order to close this gap, this study intends to investigate how language and discourse in Girls represent female strength, agency, and solidarity. The study uses a descriptive qualitative design to analyze the song lyrics using Michelle Lazar's (2014) FCDA framework, with de Beauvoir's (2011) existentialist feminist theory and Hook’s (1984, 1994, 2000) feminist theories. The analysis using Fairclough’s (1989) three-level analysis includes textual analysis, discursive practice, and social practice. The results show that affective discourse that emphasizes self-worth, vulnerability, and emotional resilience, solidarity-based narratives that frame relationships as sources of empowerment, and agency-oriented verbs and metaphors that position women as active subjects are all used to construct female strength. By showing a shift in empowerment songs from individualistic ideas of strength toward relational and existential forms of empowerment, this study adds to feminist discourse studies and provides cultural and pedagogical insights into gender representation in popular music.